Evaluation of Lipid Profile and Thyroid Hormones in Breast Cancer Women: Evaluasi Profil Lipid dan Hormon Tiroid pada Wanita Kanker Payudara - Al-Husseinawi, Hadeel Ali Shamkhi; Mohammed, Anwar Shati; Kamil, Azhar Abdul adheem (Indonesian Journal on Health Science and Medicine, 2025)
Background: Breast cancer is the foremost cause of cancer-related mortality among women globally and the second most prevalent cause of cancer death among women in the United States Aim of the Study: The study aimed to determine the association between lipid and thyroid dysregulation with breast cancer. Material and Method: A total of hundred individuals were participate in this case-control study (50 women had a breast cancer, and 50 women without disease as a control group). The study was done at Al-habobi Teaching Hospital during the period from February to June 2024. The parameters were evaluated by using Cobas 111 for biochemical tests and Cobas 411 for hormones. The Results: The study showed all level of lipid profile increased significantly in cancer patients than control group, with except the level of HDL decreased significantly in breast cancer patient. With regard thyroid hormones the study noted only the T4 decreased significantly in breast cancer patient than control group, while the other hormones not effected by disease. Conclusion: The present study concluded that lipid levels are significantly affected in women with breast cancer, while thyroid hormones are not affected by the disease Highlights: Breast cancer is a leading cause of global female mortality. Assess lipid and thyroid dysregulation association with breast cancer. Lipid levels significantly altered; thyroid hormones mostly unaffected in breast cancer. Keywords: Breast Cancer, Lipid Profile, Thyroid Hormones